Is the Prevalence of the Factor V Leiden Mutation in Patients with Pulmonary Embolism and Deep Vein Thrombosis Really Different? - Turkstra, Franktien; Karemaker, Rosa; Kuijer, Philomeen M. M.; Prins, Martin H.; Büller, Harry R. (Thrombosis and Haemostasis, 1999)
Introduction. Previous investigations have suggested a lower prevalence of the factor V Leiden mutation in patients with pulmonary embolism, as compared to patients with deep leg vein thrombosis. Methods. We studied unselected patients with pulmonary embolism, in whom we also assessed the presence of deep vein thrombosis by ultra-sonography. We assessed the prevalence of heterozygosity for the factor V Leiden mutation and compared the outcome of patients with a normal ultrasound (primary pulmonary embolism) to those with an abnormal ultrasound (combined form of venous thromboembolism). Furthermore, we performed a literature search to identify all articles regarding the prevalence of heterozygous factor V Leiden mutation in patients with primary deep vein thrombosis, primary pulmonary embolism and a combined form of venous thromboembolism. We calculated a (common) odds ratio for these 3 manifestations of venous thromboembolism, including the current findings. Results. In 92 patients with proven pulmonary embolism, 25 (27%) had also an abnormal ultrasound. In these patients, the prevalence of the factor V Leiden mutation was 24% (95% CI 9%-45%), whereas the mutation was present in 5 of 67 patients with primary pulmonary embolism (7%; 95% CI 2%-16%). The literature analysis indicated the common odds ratio for the presence of heterozygous factor V Leiden mutation in patients with primary deep vein thrombosis, primary pulmonary embolism and the combined form of venous thromboembolism to be 7.9 (95% CI 5-12), 3.5 (95% CI 2-6) and 6.8 (95% CI 3-14), respectively. Conclusion. In patients with primary pulmonary embolism the prevalence of the factor V Leiden mutation appears to be half of that reported in patients with primary deep vein thrombosis. The mechanism remains unclear.